Influence of time on the predictive value of the post-resuscitation ECG. (2nd October 2021) - Evans, Carl; Nelson, Magnus
Abstract : Background: The reliability of the electrocardiogram (ECG) after return of spontaneous circulation (ROSC) is unclear. While its predictive value has previously been described, no studies have looked at the influence of time on the post-ROSC ECG. Aim: This study aimed to evaluate the predictive value of the ECG immediately after ROSC and between 1 and 5 hours later to assess whether time influences its ability to accurately predict the need for percutaneous coronary intervention. Methods: A single-centre, retrospective, observational 1-year analysis examined the records of post-ROSC patients who underwent coronary angiography and for whom prehospital and delayed post-ROSC ECGs were available for analysis. Findings: Forty-two post-ROSC ECGs were reviewed alongside angiographic findings. Sensitivities of 25% and 69%, specificities of 60% and 100% and an accuracies of 33% and 76% were calculated for the prehospital and delayed hospital ECGs respectively. A chi-squared value of 7.78 (P=0.0053) suggests there is statistical significance between the two. Conclusions: The delayed post-ROSC ECG is statistically significantly more accurate, suggesting that time influences the reliability of the post-ROSC ECG.